The Stacks project

Lemma 15.14.8. Let $A$ be absolutely integrally closed. Let $I \subset A$ be an ideal. Then $(A, I)$ is a henselian pair if (and only if) the following conditions hold

  1. $I$ is contained in the Jacobson radical of $A$,

  2. $A \to A/I$ induces a bijection on idempotents.

Proof. Let $f \in A[T]$ be a monic polynomial and let $f \bmod I = g_0 h_0$ be a factorization over $A/I$ with $g_0$, $h_0$ monic such that $g_0$ and $h_0$ generate the unit ideal of $A/I[T]$. This means that

\[ A/I[T]/(f) = A/I[T]/(g_0) \times A/I[T]/(h_0) \]

Denote $e \in A/I[T]/(f)$ the element correspoing to the idempotent $(1, 0)$ in the ring on the right. Write $f = (T - a_1) \ldots (T - a_ d)$ with $a_ i \in A$. For each $i \in \{ 1, \ldots , d\} $ we obtain an $A$-algebra map $\varphi _ i : A[T]/(f) \to A$, $T \mapsto a_ i$ which induces a similar $A/I$-algebra map $\overline{\varphi }_ i : A/I[T]/(f) \to A/I$. Denote $e_ i = \overline{\varphi }_ i(e) \in A/I$. These are idempotents. By our assumption (2) we can lift $e_ i$ to an idempotent in $A$. This means we can write $A = \prod A_ j$ as a finite product of rings such that in $A_ j/IA_ j$ each $e_ i$ is either $0$ or $1$. Some details omitted. Observe that $A_ j$ is absolutely integrally closed as a factor ring of $A$. It suffices to lift the factorization of $f$ over $A_ j/IA_ j$ to $A_ j$. This reduces us to the situation discussed in the next paragraph.

Assume $e_ i = 1$ for $i = 1, \ldots , r$ and $e_ i = 0$ for $i = r + 1, \ldots , d$. From $(g_0, h_0) = A/I[T]$ we have that there are $k_0, l_0 \in A/I[T]$ such that $g_0 k_0 + h_0 l_0 = 1$. We see that $e = h_0 l_0$ and $e_ i = h_0(a_ i) l_0(a_ i)$. We conclude that $h_0(a_ i)$ is a unit for $i = 1, \dots ,r$. Since $f(a_ i) = 0$ we find $0 = h_0(a_ i)g_0(a_ i)$ and we conclude that $g_0(a_ i) = 0$ for $i = 1, \ldots , r$. Thus $(T - a_1)$ divides $g_0$ in $A/I[T]$, say $g_0 = (T - a_1) g_0'$. Set $f' = (T - a_2) \ldots (T - a_ d)$ and $h'_0 = h_0$. By induction on $d$ we can lift the factorization $f' \bmod I = g'_0 h'_0$ to a factorization of $f' = g' h'$ over over $A$ which gives the factorization $f = (T - a_1) g' h'$ lifting the factorization $f \bmod I = g_0 h_0$ as desired. $\square$

Comments (0)

Post a comment

Your email address will not be published. Required fields are marked.

In your comment you can use Markdown and LaTeX style mathematics (enclose it like $\pi$). A preview option is available if you wish to see how it works out (just click on the eye in the toolbar).

Unfortunately JavaScript is disabled in your browser, so the comment preview function will not work.

All contributions are licensed under the GNU Free Documentation License.

In order to prevent bots from posting comments, we would like you to prove that you are human. You can do this by filling in the name of the current tag in the following input field. As a reminder, this is tag 0DCT. Beware of the difference between the letter 'O' and the digit '0'.